Exploratory factor analysis: validity and reliability of technology self-efficacy instrument - Noh Mustafa, Fatin Syahirah; Razali, Fazilah; Mohd Puad, Mohd Hazwan (Human Resource Management Academic Research Society, 2023)
This study intends to establish the validity and reliability of the instrument for assessing the notion of teacher’s technology self-efficacy. A quantitative method was employed in the cross-sectional survey research design with data from the pilot study collected from 100 secondary school teachers in Selangor, Malaysia. The samples were determined using a stratified random sampling approach. In this research, the teachers’ technology self-efficacy instrument was utilized to assess the self-efficacy of teachers in using technology and the Digital Educational Learning Initiatives Malaysia (DELIMa) 2.0 in their teaching practice. The number of components and factor loading values for each item in the technology self-efficacy construct were determined using the Exploratory Factor Analysis (EFA). The EFA findings show five components for the construct of teachers’ technology self-efficacy, each of which has an eigenvalue greater than 1.0. i.e, (based on ISTE-NETS standards) (1) Design & Develop Digital Age-Learning Experiences and Assessments, (2) Engage in Professional Growth and Leadership, (3) Promote and Model Digital Citizenship, (4) Model Digital-Age Work and Learning, (5) Engage in Professional Growth and Leadership. The reliability of component 1 is 0.942, of the component 2 is 0.932, of component 3 is 0.768, of component 4 is 0.842 and of component 5 is 0.682. The reliability for the overall construct of teachers’ technology self-efficacy was 0.931. The complete construct of teachers’ technology self-efficacy has met the criteria for construct validity and reliability. To sum up, other researchers can utilise the study’s measures to assess the notion of teachers’ technology self-efficacy in different circumstances.